Instrumentos jurídicos do MDL - mecanismo de desenvolvimento limpo na implementação de reserva legal para fins energéticos no Brasil - Cataneo, Pedro Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Earth and its forms of life would not be the same without greenhouse effect. Some researchers estimate that without greenhouse effect Earth temperature would be very low, in an average of -32°C e -23°C, and life, as we know it, would have never appeared. The greenhouse effect is a physical proccess by which the presence of atmospheric gases makes Earth to maintain higher balanced temperature than it would have if they were absent. The global heating refers to the continuous and large period increasing of this balanced temperature. Thus, the presence of the gases of greenhouse effects is not a problem. The problem appears in its lack of control, making possible the global heating in such a level which global climate would significantly be modified. This overstated global heating risk became higher after Industrial revolution while there was a increase of fossil fuel us in the means of production raising a lot the concentration levels of carbon dioxide (CO2), wich is the greenhouse effect main gas in atmosphere. The Brazilian Climate Changes Forum aims to aware and move society to the discussion and decision making on these problems that arising out of climate change by gases of greenhouse effect, as well as on the Clean Development Mechanism (CDM) defined in article 12 of the Protocol of Kyoto to the United Nations Framework Convention about Climate Change, confirmed by the Brazilian National Congress through the Legislative Decree n° 1, of February 3rd, 1994. The Brazilian Federal Constitution of 1988 emphasizes in its article 225 that everyone has the right to have an ecological balanced environment, a common use and essential welfare to the quality of a healthy life behooving to the Political Authorities and community to defend it in current days and for the future. Therefore, the questioning of global heating loses its characteristics of calling environment scholars... (Complete abstract click electronic access below)
Keywords: Mudanças climaticas - Brasil; Direito ambiental internacional - Brasil